Characteristics of Reconstituted Tight Junctions After Corneal Epithelial Wounds and Ultrastructure Alterations of Corneas in Type 2 Diabetic Rats. (2nd June 2016) - Huang, Chenchen; Liao, Rongfeng; Wang, Feng; Tang, Songtao
Abstract: Purpose : To investigate the characteristics of reconstituted tight junctions after corneal epithelial wounds and ultrastructure alterations of corneas in a high-fat diet combined with streptozocin (STZ)-induced rat model of type 2 diabetes mellitus (DM). Materials and Methods : One-hundred Sprague-Dawley male rats were randomly divided into diabetic and normal control groups ( n = 50 each). A high-fat diet combined with intraperitoneal STZ injection was used to induce type 2 DM. Wound healing was determined using an in vivo corneal epithelial debridement model. Scanning electron microscopy (SEM) was used to study differences in corneal epithelium between diabetic and normal rats. The rate of corneal wound healing was observed by fluorescein and hematoxylin and eosin staining. Diabetic and healthy rats were sacrificed before debridement and 16, 48, 72, and 120 hours afterwards for Western blot and immunofluorescence. Results : Corneal epithelial cell connection abnormalities, dropsy, and microvillus reduction were evident by SEM. Corneal epithelial wound closure rates were decreased in diabetic rats compared with normal rats. Immunofluorescence and Western blot analysis demonstrated that occludin expression in the corneal epithelium of the diabetic group was weaker compared to the normal group at the 16 and 48 hour time-points after debridement. Conclusions : Abnormal occludin expression may contribute to delayed epithelial wound healing in diabetic corneas.